2001
DOI: 10.1007/s004640090021
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient laparoscopic adrenalectomy in patients with Conn's syndrome

Abstract: Laparoscopic adrenalectomy can be a fast operation. It is feasible and safe and yields satisfactory results for patients as an outpatient procedure when the necessary surgical experience and optimal anesthesia are both available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 17 publications
1
27
0
6
Order By: Relevance
“…In such settings, outpatient laparoscopic adrenalectomy is possible in selected cases: patients under the age of 65 years, tumors of less than 6 cm in diameter, no significant cardiorespiratory disease, first case of the day to be managed in the surgical program, residence less than 30 minutes from the hospital by car, and treatment with no more than three antihypertensive agents. [21][22][23] Patients should be treated with a MRA and potassium supplements to lower BP and to correct hypokalemia before surgery. Preoperative mineralocorticoid receptor blockade for a few weeks before surgery may also decrease the risk of postoperative hypoaldosteronism due to the chronic suppression of aldosterone secretion in the contralateral gland.…”
Section: Unilateral Adrenalectomymentioning
confidence: 99%
“…In such settings, outpatient laparoscopic adrenalectomy is possible in selected cases: patients under the age of 65 years, tumors of less than 6 cm in diameter, no significant cardiorespiratory disease, first case of the day to be managed in the surgical program, residence less than 30 minutes from the hospital by car, and treatment with no more than three antihypertensive agents. [21][22][23] Patients should be treated with a MRA and potassium supplements to lower BP and to correct hypokalemia before surgery. Preoperative mineralocorticoid receptor blockade for a few weeks before surgery may also decrease the risk of postoperative hypoaldosteronism due to the chronic suppression of aldosterone secretion in the contralateral gland.…”
Section: Unilateral Adrenalectomymentioning
confidence: 99%
“…Edwin et al (10) reported that laparoscopic adrenalectomy with transabdominal lateral flank approach can be safely performed in an outpatient setting, with surgical experience, patient selection and optimal anesthesia, in their case series of 13 patients (11). Lee et al (12) did not observe adrenal insufficiency in 13 patients with bilateral pheochromocytoma who underwent cortex sparing adrenal surgery, with recurrences in only three patients.…”
Section: Case Presentationmentioning
confidence: 99%
“…Currently, laparoscopic adrenalectomy is not advised for primary malignant or larger than 5 cm adrenal tumours. Edwin et al [21] report 13 day-case laparoscopic adrenalectomies for Conn's tumours. Laparoscopic adrenalectomy can be performed through the transperitoneal or retroperitoneal approach.…”
Section: Commentsmentioning
confidence: 99%